Case report: Simultaneous resections of pulmonary segment and an esophageal leiomyoma during spontaneous ventilation video-assisted thoracoscopic surgery - Ding, Yi; Shan, Lei; Li, Peichao; Li, Ning; Zhang, He; Cong, Bo; Zhang, Hua; Tian, Zhongxian; Zhao, Xiaogang; Zhao, Yunpeng (Frontiers in Oncology, 2024)
Spontaneous ventilation video-assisted thoracoscopic surgery (SV-VATS) has rapidly developed in recent years. The application scope is still being continuously explored. We describe a case in which a 40-year-old woman with mixed ground-glass opacity (GGO) and an esophageal leiomyoma successfully underwent simultaneous segmentectomy and leiomyoma resection through spontaneous ventilation video-assisted thoracoscopic surgery.The perioperative course was uneventful. Postoperative pathology revealed minimally invasive adenocarcinoma and esophageal leiomyoma.